Developing Mathematics Teaching Materials on SPLDV Materials by Combining The Scientific Approach And The RME Approach To Improve Metacognitive Ability and Learning Independence of Junior High School Students - Sigit Mulqiyono; Wahyu Hidayat; Euis Eti Rohaeti (IKIP Siliwangi, 2022)
This study aims to develop teaching material in the form of a mathematics learning module on SPLDV material and to improve students' metacognitive abilities and also students' learning independence. This research was conducted in four junior high schools as a place for the initial field test, the main field test, and the operational field test. The indicator of the success of this research is seen from the level of validation given by the validator, namely material experts and media experts of 75%. As for the success of learning, it can be seen from the significance obtained from the statistical test results from the results of the metacognitive ability test and student learning independence questionnaire. The results of this development research showed that: 1) The results of the validation test of the two experts found that the teaching materials developed were in good classification with a percentage of 89.4% for material experts and 83.3% for media experts. This means that the teaching materials meet the classification to good practice and implementation. So it is feasible to use and be tested. 2) At the product trial stage, students' responses to the teaching materials were quite good with a percentage of 81.28% for the initial field trial and 83.01% for the main field test. Student responses to learning using the teaching materials that were developed also had good criteria at the time of operational trials with a percentage of 78%, 3) from the results of statistical tests with a significance level of 0.05, metacognitive abilities, and student learning independence using the developed teaching materials had increased. significant. So that the development of teaching materials can affect the mastery of students' mathematical and affective abilities.